2020
DOI: 10.3390/antiox9121173
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorn Herbal Preparation from Crataegus oxyacantha Attenuates In Vivo Carbon Tetrachloride -Induced Hepatic Fibrosis via Modulating Oxidative Stress and Inflammation

Abstract: Hawthorn (HAW) is a herbal preparation extracted from Crataegus oxyacantha. HAW has cardioprotective, antioxidants, anti-inflammatory, and anti-hypotensive effects. HAW’s effect on hepatic fibrosis remains, however, unknown. This study evaluated the impact of HAW on carbon tetrachloride (CCl4)-induced hepatic fibrosis in rats and elucidated its mechanisms. HAW reduced liver index and the serum liver enzyme markers and reduced liver damage, and fibrosis as confirmed by histopathological scoring of hematoxylin-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…This potency was related to the phenolic content of VVPF, including vanillic, gallic, caffeic, p -coumaric, syringic, ferulic, salicylic, and ellagic acids, along with the flavonoids and resveratrol 2 . These compounds have not only neutralized the ROS produced from CCl 4 metabolism but also enhanced the antioxidant indices in all the studied organs 36 42 . The heatmap figures found that the improvement of the antioxidant defense system by VVPF in the lung tissue was higher than in other studied organs (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…This potency was related to the phenolic content of VVPF, including vanillic, gallic, caffeic, p -coumaric, syringic, ferulic, salicylic, and ellagic acids, along with the flavonoids and resveratrol 2 . These compounds have not only neutralized the ROS produced from CCl 4 metabolism but also enhanced the antioxidant indices in all the studied organs 36 42 . The heatmap figures found that the improvement of the antioxidant defense system by VVPF in the lung tissue was higher than in other studied organs (Fig.…”
Section: Discussionmentioning
confidence: 92%
“… 35 It has been reported that carbon tetrachloride is reversed by natural products in mammals. 36 , 37 Standardized extract of ginger relieves liver cancer via enhancing apoptosis and repressing proliferation by inhibiting oxidative stress and inflammation signaling. 38 Induced reproductive toxicity can be associated with chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , similar results were observed. It was reported that CCl4 increased oxidative stress and led to cell death in vitro ( Hamza et al, 2020 ). Here, we used CCl4 to treat NCTC 1469 cells, a murine normal hepatic cell line, and found that the ROS level and death of NCTC 1469 increased.…”
Section: Discussionmentioning
confidence: 99%